Diagnósticos de enfermagem associados a qualidade de vida relacionada à saúde de mulheres com câncer de mama - Naziazeno, Shirley Dósea dos Santos (2017)
Introduction: Breast cancer is a neoplasm feared by women to have intense repercussions on their physical, social and emotional condition. Quantitative measures to assess health-related quality of life are essential for the detection of adverse reactions caused by the diagnosis and treatment of breast cancer. Knowledge of changes in health-related quality of life favors the identification of specific nursing diagnoses for the oncology area, which makes it possible to standardize care and strengthen nursing practice, based on scientific evidence. General objective: To associate nursing diagnoses with the health problems of women with breast cancer undergoing chemotherapy identified from HRQoL instruments. Specific objectives: To evaluate the HRQoL of women with breast cancer undergoing chemotherapy; To identify health problems through instruments for the evaluation of HRQoL in women with breast cancer in chemotherapy; To verify the nursing diagnoses, NANDA-I taxonomy, version 2015-2017. Method: Descriptive, exploratory, cross - sectional study with quantitative approach. Performed in two public oncology services, with 75 participants. Four instruments were used to collect data: Sociodemographic and clinical characterization; European Organization for Research and Treatment of Cancer Core Cancer Quality Life Questionnaire (EORTC QLQC30); Breast Cancer Specific Module (EORTC-BR23) and the instrument for validation of nursing diagnoses. For the descriptive analysis software R 3.1.2 was used. Cronbach's alpha was calculated to test the answers obtained through the questionnaires. From the health problems detected through the EORTC instruments, the prevalent nursing diagnoses were identified. The association of health problems with nursing diagnoses was submitted to content validation. Five judges were selected using the Fehring criteria. The Excel software, version 2016 MSO, was used for simple descriptive statistical analysis. For the validation of content, the coefficient of agreement Tau (τ) of Kendall and the Index of Content Validity (IVC) was used. Results: The most affected areas of health-related quality of life were financial difficulty (59.11), emotional function (58.78), sexual pleasure (56.94), insomnia (44.44), side effects of systemic therapy (36.00), pain (34.44) and fatigue (30.96). We identified 21 health problems that presented frequency greater than 50% and these were associated with 13 nursing diagnoses. Only two nursing diagnoses presented CVI lower than 0.75: Impaired Comfort and Acute Pain. Conclusion: Breast cancer and chemotherapy treatment interfered in the quality of life related to women's health. The domains of health-related quality of life most affected were generally classified as regular. The most prevalent health problems were: "Difficulty in making great efforts", "Need to rest", "Concern about future health", "Financial difficulties", "Absence of sexual desire" and "Absence of sexual relations". The predominant nursing diagnoses were Fatigue, Acute Pain and Chronic Pain.